2021
DOI: 10.3390/ijms222212483
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferases SUV39H1 and G9a and DNA Methyltransferase DNMT1 in Penumbra Neurons and Astrocytes after Photothrombotic Stroke

Abstract: Background: Cerebral ischemia, a common cerebrovascular disease, is one of the great threats to human health and new targets for stroke therapy are needed. The transcriptional activity in the cell is regulated by epigenetic processes such as DNA methylation/demethylation, acetylation/deacetylation, histone methylation, etc. Changes in DNA methylation after ischemia can have both neuroprotective and neurotoxic effects depending on the degree of ischemia damage, the time elapsed after injury, and the site of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Recently, the role of epigenetic mechanism in the regulation of gene transcription in stroke has been clearly revealed [26,33]. The current data showed the elevation of DNMT1 and HDAC3 in cerebral ischemia corresponding with the changes in the previous studies [34][35][36][37][38][39]. These changes are associated with brain edema [40], neuronal loss, neuronal deficit, and neuronal recovery in cerebral ischemia [41].…”
Section: Discussionsupporting
confidence: 60%
“…Recently, the role of epigenetic mechanism in the regulation of gene transcription in stroke has been clearly revealed [26,33]. The current data showed the elevation of DNMT1 and HDAC3 in cerebral ischemia corresponding with the changes in the previous studies [34][35][36][37][38][39]. These changes are associated with brain edema [40], neuronal loss, neuronal deficit, and neuronal recovery in cerebral ischemia [41].…”
Section: Discussionsupporting
confidence: 60%
“…In neuronal cell death including apoptosis after stroke, DNMTs, DNMT1, and DNMT3a expression regulates increased or decreased global DNA methylation [ 8 , 9 , 12 , 26 , 58 , 143 ]. Fetal hypoxia induced a decrease in GR expression by increased DNA methylation in the hippocampus of neonatal mice, as well as increased susceptibility of the brain to hypoxia–ischemic injury [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another animal model of photothrombotic stroke (PTS), the level of DNMT1 was increased in the nuclear fraction of neurons and in the cytoplasmic fraction of astrocytes in the penumbra tissue at 24 h after PTS induction; furthermore, apoptosis was induced. Inhibition of DNMT1 by 5-aza-dC protected against PTS-induced apoptosis in the penumbra at 4 days, as well as 24 h after PTS [ 58 ]. The effect of altered DNA methylation using 5-aza-dC on neuronal apoptosis was also confirmed in an experiment with mouse hippocampus-derived neuronal HT22 cells.…”
Section: Dna Methylation In Neuroprotection After Strokementioning
confidence: 99%
“… Endres et al (2000) found that DNA methylation levels were upregulated after focal cerebral ischemia and correlated with poor prognosis. Pharmacological inhibition or gene knockout of DNA methyltransferases (DNMTs) can alleviate ischemic brain injury and increase neuronal survival ( Dock et al, 2015 ; Sharifulina et al, 2021 ). In our study, cerebral I/R treatment may increase DNA methylation, resulting in decreased LAPTM5 expression.…”
Section: Discussionmentioning
confidence: 99%